The Shriek of Silence : A Phenomenology of the Holocaust Novel - Patterson, David, 1948- (Book collections on Project MUSE., 2015)
""In the Holocaust novel, silence is always a character, and the word is always its subject matter."" So writes David Patterson in this profound and original study of more than thirty important writers. Contrary to existing views, he argues, the Holocaust novel is not an attempt to depict an unimaginable reality or an ineffable horror. It is, rather, an endeavor to fetch the word from silence and restore it to meaning, to resurrect the human soul, to regenerate the relation between the self and God, the self and other, the self and itself. This book is less a critical study in the usual sense t.